The analysis of the relationship between respiratory functions and body compositions of alpine discipline and cross-country skiing athletes - Buket Sevindik Aktaş (Turkish Journal of Kinesiology)
The aim of this study was to evaluate the relationship between respiratory functions and body compositions of elite athletes in alpine disciplines and cross-country skiing through their comparison. The study included 32 male athletes (age: 18.3±2 year, height: 172.1±6.05 cm, body weight: 65.73±10.79 kg, and body mass index (BMI): 22.91±2.80 kg/m2) within the scope of alpine disciplines and cross-country skiing. The heights of the athletes were measured with a stadiometer (Holtain, UK) with an accuracy of ±1mm. The weights of the athletes and BMI values were measured using a Tanita brand (BC, 418 Tanita, Japan) body composition analyzer with a precision of 100 grams. The respiratory function and respiratory muscle strength of the athletes were evaluated using a digital spirometer (Pony FX Cosmed, Italy). Pearson's correlation analysis was used to determine the relationships between respiratory functions and anthropometric structures of the groups. The results indicated that cross-country skiing athletes had higher averages in FVC, FEV1, FEV1/FVC, PEF, MIP, MVV, and MEP parameters compared to alpine discipline athletes, with only the MIP value being higher in alpine discipline athletes. The results revealed positive correlations between age and FVC (0.563), FEV1 (0.521), PEF (0.679), and MVV (0.511) in cross-country skiing athletes. Negative correlations were found between body weight and FEV1/FVC (r=0.578), FEV1/FVC (r=0.545), height and MVV (r=0.541), and body mass index and FEV1/FVC (r=0.541), FEV1/FVC (r=0.676) in cross-country skiing and alpine discipline athletes, respectively (p0.05). In order to achieve maximum performance, it is very important to identify and keep under control the factors affecting respiratory functions. The current study demonstrated that the characteristics of the sport have an impact on physiological changes in the respiratory system and also affect body compositions and respiratory functions.